Linguistic and cultural identity of Indonesian Americans in The United States - Lie, Anita; Wijaya, Juliana; Kuntjara, Esther (Indonesian Journal of Applied Linguistics, 2018)
This article examines the second-generation immigrants in California and focuses on their language use and cultural identity as Indonesian-Americans. This study investigated to what extent home language use and community involvement influenced mastery of Indonesian heritage language and what factors affected the forming of cultural identity. Data were drawn from self-assessed Indonesian Oral Proficiency Questionnaire and in-depth interviews of sixteen Indonesian-Americans aged fifteen to early twenties.  Their parents were also interviewed as triangulation.  Results show that parents’ insistence in using Indonesian as home language and the youths’ investment in support community have enhanced the mastery of Indonesian heritage language.  Furthermore, exposure to the language and culture, investment, and community factors have affected the transformation of cultural identity.